Green Intellectual Capital, Asset Growth on Stock Return: Role Financial Performance as Intervening - Agustina, Sri; Ruhiyat, Endang; Sugiyanto, Sugiyanto (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – The Purpose of study was to determine the effect of green intellectual capital on stock returns with financial performance as an intervening variable. Metodelogy – This study uses a sample of agricultural sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The sampling technique used purposive technique, the samples obtained were 20 agricultural sector companies or 100 data observations. The analysis method used is panel data regression analysis and path analysis using Eviews.12. Findings – Based on the research results, it shows that together green intellectual capital, asset growth and financial performance have an effect on stock returns. Meanwhile, partially asset growth has a positive and significant effect on stock returns. Financial performance has a positive and significant effect on stock returns. Green intellectual capital has no effect on stock returns. Green Intellectual capital has a positive and significant effect on financial performance. Asset growth has no effect on financial performance. Financial performance is able to mediate the effect of green intellectual capital on stock returns. Financial performance is unable to mediate the effect of asset growth on stock returns.